The thief of time philosophical essays on procrastination - Andreou, Chrisoula; White, Mark D., 1971- (New York ; Oxford : Oxford University Press, 2010)
When we fail to achieve our goals, procrastination is often the culprit. But how exactly is procrastination to be understood? This edited volume integrates the problem of procrastination into philosophical inquiry, exploring the relationship of procrastination to agency, rationality, and ethics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Procrastination